Assessing Satellite Resilience: SPN and CTMC Models for Availability Evaluation - Bermudez, Esau; Maciel, Paulo (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2024)
Satellite communications have become an integral part of our daily lives, and the focus on satellite telecommunications is expected to grow in prominence. This paper presents a Stochastic Petri Nets (SPN) model for availability, where transitions between satellite states (operational, maintenance, and failure) are modeled as stochastic processes using Erlang distributions. This approach effectively captures uptime, failures, and repairs, providing a more accurate representation of satellite aging and its impact on availability, especially compared to the non-aging model proposed by NAVSTAR and NASA. Thus, the resilience of satellites relies on their ability to manage scheduled (maintenance) and unscheduled (sudden failures) outages.